Antecedents of Exercise Dependence in Ultra-Endurance Sports: Reduced Basic Need Satisfaction and Avoidance-Motivated Self-Control - Schüler, Julia; Knechtle, Beat; Wegner, Mirko (Frontiers in Psychology, 2018)
Initiating and maintaining sports and exercise behaviour are usually discussed in terms of strategies for promoting health. In the present study, we analysed a sample of extreme endurance sport athletes and set out to predict exercise addiction, which is a facet of a sport-related health risk. We therefore draw on self-determination theory (Deci & Ryan, 1985, 2000), according to which low basic psychological need satisfaction can lead to excessive compensatory behaviour. We aim to disentangle the effects of need satisfaction in the activity itself (exercising) and outside the activity (work/leisure) on exercise addiction. Furthermore, we propose anxious self-motivation as a mediator and tested whether it links low basic need satisfaction with exercise dependence. A correlational study with 323 multi-triathlon athletes confirmed our hypothesis that need satisfaction in work/leisure (but not in sports) is negatively related to exercise addiction. Furthermore, only need for competence in both domains (sport, work/leisure) is associated with anxious self-motivation. Mediation models showed that low competence satisfaction leads to anxious self-motivation that in turn predicts exercise addiction. The results are discussed critically in terms of their practical and theoretical implications for promoting health through sport and exercise.